Young Citizens of the World Unite! A Case for the Model United Nations in Middle School Classrooms - Stacie K Pettit; Craig D Albert; Juan Walker; Laura Rychly (Middle Grades Review, 2017)
In this manuscript, the authors describe the benefits and theoretical connections the Junior Model United Nations (JMUN) program has with middle school classrooms. The lens used to view the JMUN program is informed by literature on the needs of young adolescents, inquiry learning, and global citizenship. Findings from this literature illuminate nuances in the interaction between inquiry learning through the C3 Framework and active learning participation. Implications for middle school students, in-service teachers, and teacher candidates are discussed.
Keywords: critical literacy; global mindedness; inquiry learning process; engagement; simulation; application of knowledge; global citizenship; middle school education; social studies education; Junior Model United Nations; active learning; C3 framework